Le regioni rosse nell'Europa continentale. Un'epopea del Novecento - Caciagli, Mario (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
As a phenomenon of the XX Century, the few existed mass parties were capable to build territorial political sub-cultures. The cornerstone of the subcultures was the capacity to implant itself in specific regions. In Germany from the end of the XIX Century until the rise to power of the Nazis Red Regions were Thuringia, Saxe and Berlin under socialist hegemony, and then under communist influence too. The Red Region in Austria coincided with Vienna and was also destroyed from the fascist reaction. In France the Red Region was the banlieue of Paris, where the Communist Party was predominant from the ‘30 to the ‘70, when working class and communist subculture disappeared because the de-industrialization. The Red Regions in Italy have had a longer wife, because the different social classes of composition and different electoral support. Economic and social changes as the dissolution of the Soviet World have been causes of the end.